Engaging, Binding and Retaining Nurses: The Success Formula of an Exemplary Ward - D.A.E. Spoolder; A.G. van Duijn; H.A. Schreuder-Cats; M.J. de Bie-Timmer (SAGE Open Nursing)
Background Nurse staffing remains an ongoing issue in healthcare worldwide. However, a Dutch urology ward has hardly any staffing difficulties. Nevertheless, it remains challenging to grasp what exactly is the success formula of the ward. Investigating a practical example of a successful ward will facilitate a deeper understanding of the application of current knowledge. Furthermore, novel concepts offer potential solutions to current problems. There is a need of putting the knowledge into practice. Objective The objective is to identify the factors that contribute to the success of the urology ward in engaging, binding, and retaining nurses, to provide practical insights and opportunities for other wards. Methods The Dutch Model for Excellent Care forms the basis of a prospective, qualitative research study with focus groups. Twelve nurses were divided into three focus groups, based on work experience. They were asked about why they love working on the ward. Analysis was performed using Braun and Clarke's method for thematic analysis. Emerged themes were presented, substantiated by quotes. Results Four themes and twelve subthemes became apparent: (a) Supportive structures: nursing governance, professional development, and quality of leadership. (b) Optimal work environment: working with skilled nurses, a professional relationship with physicians and professional autonomy. (c) Team culture: feeling seen, good ambiance, and equality. (d) Specialty of urology: variation in work, workload, and the type of patient. Conclusions Nurses are uniquely positioned to provide invaluable insight into their needs. They illuminated the crucial importance of fostering a work environment that prioritizes both professional as well as personal needs.